Improving Arabic Vocabulary Understanding through the Drill Method at MI Darul Ulum Probolinggo - Muhammad, Devy Habibi; Marzuki, M.Hasbullah; Qodir, Abdul; Zaka, Muhammad Zakaria (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve the understanding of Arabic vocabulary among fifth-grade students at MI Darul Ulum, Probolinggo Regency, through the drill method. The research employed a Classroom Action Research (CAR) design following Kemmis and McTaggart’s two-cycle model, involving 25 students (n=25). Data were collected through observations, vocabulary tests, interviews, and documentation, and analyzed both qualitatively and quantitatively. Quantitative data were drawn from vocabulary test scores, while qualitative analysis examined student motivation and participation. In Cycle I, only 8 students (32%) achieved the minimum completeness criterion (KKM) with a mean score of 64.3. After revising instructional activities in Cycle II, 13 students (52%) met the KKM and the mean score increased to 72.6. In Cycle III, 22 students (88%) achieved mastery with an average score of 83.4, reflecting a consistent improvement in vocabulary understanding and engagement. The findings indicate that the drill method demonstrated a consistent improvement in students’ Arabic vocabulary mastery. Data triangulation across tests, observations, and interviews ensured reliability. The study provides practical implications for Arabic instruction, highlighting structured repetition and active participation as effective strategies to enhance vocabulary learning outcomes.